Absolutely almost - Graff, Lisa (Lisa Colleen), 1981- (Philomel Books, an imprint of Penguin Group (USA), 2014)
Ten-year-old Albie has never been the smartest, tallest, best at gym, greatest artist, or most musical in his class, as his parents keep reminding him, but new nanny Calista helps him uncover his strengths and take pride in himself.